RAPID ASSESSMENT PROTOCOL AS A PEDAGOGICAL RESOURCE FOR THE SOCIO-ENVIRONMENTAL READING OF URBAN RIVERS: ADAPTATIONS IN THE DEVELOPMENT AND VALIDATION OF A DIDACTIC GUIDE - Menezes, Helaine de Oliveira; Fontana, Felipe (Seven Editora, 2026)
This article analyzes the development, structure, and validation of a didactic guide constructed through the adaptation of a Rapid Assessment Protocol (RAP) for elementary education, seeking to address the problem of how such an instrument can promote critical environmental learning and assist students in understanding the socio-ecological determinants of urban river degradation. Grounded in a qualitative approach, the study combined documentary analysis, methodological adaptation of the RAP, pedagogical workshops, and field activities conducted with students from a public school in Janiópolis, Paraná (Brazil). The theoretical framework engages with references on urban water resources (Tucci, 2008; Tundisi, 2014; 2020), Rapid Assessment Protocols (Callisto et al., 2002; Guimarães, Rodrigues & Malafaia, 2012), and Critical Environmental Education (Guimarães, 2004; Layrargues & Lima, 2014), as well as the principles of the National Water Resources Policy and Sustainable Development Goal 6 (SDG 6). The results indicate that the guide fostered a critical reading of the Água dos Peões stream, enhanced students’ interpretive capacity, strengthened their understanding of anthropogenic pressures, and stimulated argumentative positioning in relation to local environmental conflicts. The product proved to be scientifically and pedagogically robust, with high potential for replication in public schools and practical relevance – particularly in terms of public management – for small municipalities. It is concluded that the guide constitutes a relevant educational technology for improving school-based environmental management, fostering social participation, and supporting formative practices aligned with the National Water Resources Policy, the SDGs, and critical perspectives in Environmental Education, thereby justifying its academic, public, and social significance.